Predicting the effectiveness of oil recovery strategies in the marine polluted environment. (1st October 2018) - Giacoletti, A.; Cappello, S.; Mancini, G.; Mangano, M.C.; Sarà, G.
Abstract: Many recent studies have focused their attention on the physiological stress experienced by marine organisms in measuring ecotoxicological responses. Here we suggest a new approach for investigating the effects of an anthropogenic pollutant on Life-History (LH) traits of marine organisms, to provide stakeholders and policy makers an effective tool to evaluate the best environmental recovery strategies and plans. A Dynamic Energy Budget (DEB), coupled with a biophysical model was used to predict the effects of a six-month oil spill on Mytilus galloprovincialis' LH traits and to test two potential recovery strategies in the central Mediterranean Sea. Oxygen consumption rates were used to check for increasing energetic maintenance costs [ṗM ] respectively in oil-polluted system treatments (∼76.2%) and polluted systems with physical (nano-bubbles ∼32.6%) or chemical treatment (dispersant ∼18.4%). Our model outputs highlighted a higher growth reduction of intertidal compared to subtidal populations and contextually an effect on the reproductive output and on the maturation time of this latter. The models also enabled an estimation of the timing of the disturbance affecting both the intertidal and subtidal populations' growth and reproduction. Interestingly, results led to the identification of the chemical dispersant as being the best remediation technique in contexts of oil spill contamination. Graphical abstract: Highlights: Insights will provide an effective tool to evaluate environmental recovery plans. Oxygen consumption rates described the alteration of energetic costs of maintenance. DEB & a biophysical model allowed to detect effects of oil spill on LH traits. Two potential recovery strategies were tested: nanobubbles and dispersant. The chemical dispersant has been identified as the best remediation technique.